Use of a Smartphone Digital Goniometer Combined with the Freehand Pedicle-Probing Technique for Repair of a Comminuted L6 Fracture in a 4 kg Dog - Mullins, Ronan A.; Santos, Bruno; Jamont, Wiktoria (VCOT Open, 2024)
A 10-month-old, 4 kg, Bichon Frise cross was referred for surgical stabilization of a highly comminuted L6 vertebral fracture after a road traffic accident. Nonambulatory paraparesis was present, with weak voluntary motor function in both pelvic limbs. Computed tomography (CT) of T6 to Cd1 identified a highly comminuted fracture of vertebral body and cranial endplate of L6 with severe narrowing of vertebral canal. A left-sided L6 pediculectomy was performed. The cauda equina was mildly bruised. Smaller bone fragments were removed, whereas larger bone fragments were depressed ventrally. Two 1.5-mm cortical screws were inserted into pedicles of L7 and a further two 2.0-mm screws into L5 vertebral body using the pedicle-probing technique. Following exposure of underlying cancellous bone, a smartphone digital goniometer, held by a nonsterile assistant, was used to guide advancement of a blunted Kirschner wire acting as a probe according to preoperative CT-determined safe angles. Postoperative CT identified excellent vertebral column alignment with improvement in spinal cord compression and optimal placement of implants at L5 and L7 (grade 1 modified Zdichavsky). Repeat CT at 3 months postoperatively identified well-seated implants. This report highlights that use of a smartphone goniometer may be a useful adjunct to the freehand pedicle-probing technique to guide correct trajectory of the probe and may also have application in other regions of the spine.
Keywords: vertebral fracture; pedicle-probing technique; smartphone goniometer; spinal; dog